SISTEM KEPEGAWAIAN DI JEPANG - Herman Herman (Jurnal Manajemen Kepegawaian, 2007)
One of the discussion of comparative public administration is about comparative of civil service system. This article compare between Japan and Indonesian civil service system, and to find some good lessons for Indonesian civil service system. Total staff of number law, independent institution that responsibility for civil system, recruitment based on merit, promotion based on performance, and salary system based on workload, responsibility, and work complexity are positive learning to develop Indonesian civil servive system. Keywords: Civil service, performance, merit system